Evaluating vector competence for Yellow fever in the Caribbean - Gabiane, Gaelle; Bohers, Chloé; Mousson, Laurence; Obadia, Thomas; Dinglasan, Rhoel R; Vazeille, Marie; Dauga, Catherine; Viglietta, Marine; Yébakima, André; Vega-Rúa, Anubis; Gutiérrez Bugallo, Gladys; Gélvez Ramírez, Rosa Margarita; et al. (Nature Publishing Group, 2024)
Abstract The mosquito-borne disease, Yellow fever (YF), has been largely controlled via mass delivery of an effective vaccine and mosquito control interventions. However, there are warning signs that YF is re-emerging in both Sub-Saharan Africa and South America. Imported from Africa in slave ships, YF was responsible for devastating outbreaks in the Caribbean. In Martinique, the last YF outbreak was reported in 1908 and the mosquito Aedes aegypti was incriminated as the main vector. We evaluated the vector competence of fifteen Ae. aegypti populations for five YFV genotypes (Bolivia, Ghana, Nigeria, Sudan, and Uganda). Here we show that mosquito populations from the Caribbean and the Americas were able to transmit the five YFV genotypes, with YFV strains for Uganda and Bolivia having higher transmission success. We also observed that Ae. aegypti populations from Martinique were more susceptible to YFV infection than other populations from neighboring Caribbean islands, as well as North and South America. Our vector competence data suggest that the threat of re-emergence of YF in Martinique and the subsequent spread to Caribbean nations and beyond is plausible.
Keywords: Yellow fever virus (YFV); Sub-Saharan Africa ; uganda